Peran Majelis Zikir Azzikra dalam Membina Karakter Peduli Sosial dan Peduli Lingkungan - Halijah, Sarifa (Institut Agama Islam Negeri (IAIN) Bone, 2019)
This article is about the role of the Council of Remembrance Az-Zikra in the village of Macanag in the formation of social and caring environment. This research is included in the type of field research with qualitative analysis of data collection methods, observation, interviews and document tracing. The results showed that the role of the Council of Dhikr in instilling social care character is; Giving a tajwid for TPA, teenagers and housewives once every week, this program is also called al-Qur'an Tahsin, regular studies are established by the Arisan every month, giving assistance to orphans and poor, visiting the People who are sick, give attention to the people who mourn by visiting the House of Sorrow for Yasinan, Tahlilan and Ta'ziyah lectures, Yasinan and Barasanji for the community members who enter the new house/shop, Shaltty to Marriage, want to depart from Hajj or Umrah and Aqiqah, Gotong Royong every Sunday in the form of cleaning the environment around the house and mosques also KINDERGARTEN and TPA that centered on the yard of the mosque of Az-Zikra, having iftar together in turns from home to House in the month of Ramadan for every member who is able or sharing Ta'jil Iftar in the orphanage, Program Infaq for members for the construction of mosque Az-Zikra Macanang, Hatmil Qur'an event If there are officers, members, or family of managers and Members who passed away. As for the way members of the Council of Remembrance Az-Zikra realize the character cares through the way: hygiene-keeping and environmental conservation, available trash disposal and handwashing place, provide bathroom and clean water, habituation Energy saving, making Biopori in the environmental area, building wastewater well, and doing habituation separates the type of organic and inorganic waste.Artikel ini adalah tentang peran Dewan Zikir Az-Zikra di desa Macanag dalam pembentukan lingkungan sosial dan kepedulian. Penelitian ini termasuk dalam jenis penelitian lapangan dengan analisis kualitatif metode pengumpulan data, observasi, wawancara dan penelusuran dokumen. Hasil penelitian menunjukkan bahwa peran Dewan Dzikir dalam menanamkan karakter kepedulian sosial adalah; Memberikan tajwid untuk TPA, remaja dan ibu rumah tangga sekali setiap minggu, program ini juga disebut al-Qur'an Tahsin, studi reguler diadakan oleh Arisan setiap bulan, memberikan bantuan kepada anak yatim dan orang miskin, mengunjungi Orang-orang yang sakit, memberikan memperhatikan orang-orang yang berduka dengan mengunjungi Rumah Duka untuk kuliah Yasinan, Tahlilan dan Ta'ziyah, Yasinan dan Barasanji untuk anggota masyarakat yang memasuki rumah / toko baru, Shaltty to Marriage, ingin berangkat dari Haji atau Umrah dan Aqiqah , Gotong Royong setiap hari Minggu dalam bentuk membersihkan lingkungan di sekitar rumah dan masjid juga KINDERGARTEN dan TPA yang berpusat di halaman masjid Az-Zikra, berbuka puasa bersama secara bergantian dari rumah ke rumah di bulan Ramadhan untuk setiap anggota yang mampu atau berbagi Ta'jil Iftar di panti asuhan, Program Infaq untuk anggota untuk pembangunan masjid Az-Zikra Macanang, acara Hatmil Qur'an Jika ada petugas, anggota, atau keluarga manajer dan Anggota yang melewati sebuah cara. Adapun cara anggota Dewan Peringatan Az-Zikra mewujudkan karakter peduli melalui cara: menjaga kebersihan dan pelestarian lingkungan, tersedia tempat pembuangan sampah dan tempat cuci tangan, menyediakan kamar mandi dan air bersih, hemat energi pembiasaan, menjadikan Biopori di lingkungan area, membangun air limbah dengan baik, dan melakukan pembiasaan memisahkan jenis sampah organik dan anorganik.